New School, the Same Old Rut? Action Research of Unsuccessful First-Year Students in a High School - Masoń-Budzyń, Joanna (Theory and Practice of Second Language Acquisition, 2018)
Action research is one of the tools that a reflective teacher may use in order to solve specific problems they encounter in their daily teaching practice. The article describes action research carried out in a high school to investigate some of the reasons behind the poor performance of some first-year students. It has been observed that students’ lack of success during the first semester corresponds directly to their low results in the end-of-middle school exam, despite the fact that they were allocated to groups on the basis of a placement test. In a questionnaire survey students reflected upon their motivation, attitude, classroom anxiety, and assessed their performance against other group members. This article offers an analysis of the questionnaire results and attempts at presenting certain ways in which teachers could help students who did not manage to wipe the slate clean avoid some learning barriers.